Implementasi Nilai Kemuhammadiyahan melalui Pembelajaran dan Kegiatan Keagamaan di TK Aisyiyah 41 Tegalharjo: Implementation of Muhammadiyah Values through Learning and Religious Activities at Aisyiyah Kindergarten 41 Tegalharjo - Devi Indah Junitasari; Khoirul Umi Latifah; Anggi Zelsiana Dewi; Tsania Putri Raikhana; Ellina Ayuningtyas; Vita Ayu Mei Kusuma; Azkiya Fantasyiru Fadhila; Nelsya Cili Aira Rinaldi; Ahmad Nurrohim (Litera Academica Publishing, 2025)
Understanding and implementing Muhammadiyah values from an early age is very important to shape the character of every child in the Tegalharjo area so that they have noble morals and have an Islamic soul. The purpose of this study is to implement Muhammadiyah values through learning and religious activities at TK Aisyiyah 41 Tegalharjo.The method used in this research is a qualitative method, namely by collecting data through direct interviews with local residents, observation, and documentation.The results of this study show that Muhammadiyah values have been instilled by local residents from an early age,one of them is in teaching at Aisyiyah 41 Tegalharjo Kindergarten with the habit of reading Iqra', training in reading prayers, introduction to Muhammadiyah figures, memorizing daily prayers, and norms that exist in Muhammadiyah.Apart from religious activities, Muhammadiyah values are also applied in learning by painting calligraphy, learning to write Arabic letters, and learning about manners between fellow human beings.This implementation not only involves early childhood and teachers at Aisyiyah 41 Tegalharjo Kindergarten, but also the parents of the kindergarten students.Thus, it is hoped that Muhammadiyah values will continue to be instilled from an early age and will not be lost due to developments in the era. and the activities carried out can be an effective means of instilling Muhammadiyah values at an early age.